Trends in “Natural” Value-Added Calf Programs at Superior Livestock Video Auction - K. G. Odde; M. E. King; E. D. McCabe; M. J. Smith; K. L. Hill; G. M. Rogers; K. E. Fike (Kansas Agricultural Experiment Station Research Reports, 2019)
Objective:This study utilized data from Superior Livestock Video Auction to investigate trends in the use of “natural” value-added calf programs. Study Description:Nine years of data (2010-2018) were evaluated for enrollment trends in all natural programs and non-hormone treated cattle. Multiple regression was used to determine the relative value of calves enrolled in the non-hormone treated cattle program. The Bottom Line:Price advantages for non-hormone treated calves may not be sufficient to justify not using growth-promoting implants on calves.
Keywords: natural beef program; video auction; beef calves